2019
DOI: 10.20473/ijosh.v8i2.2019.139-149
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Individual Characteristics, Workload, and Noise with Work Fatigue

Abstract: Introduction: Work fatigue decreases preparedness that raises the risk of workplace accidents. Some of the factors that cause work fatigue are workers characteristics, workload and noise. The purpose of this study is to analyze the correlation between those factors and work fatigue among workers of PT Kerta Rajasa Raya in circulator loom unit. Metods: This is a descriptive observational study that uses a cross sectional approach. This study uses total sampling with a total member of 44 workers. The variables i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 2 publications
3
11
1
1
Order By: Relevance
“…The most optimum physical capacity possessed by individual is in the age of 25-30 years old and over 30 years old, physical capacity will reduce 1% per year (Tarwaka, 2014). The result of this research supported the previous research result which revealed that age has significant effect on work fatigue (Atiqoh et al, 2014;Bongakareng, Layuk, Pesak & Danial, 2019;Rahmawati & Tualeka, 2019). This research result was not in line the research conducted by Putri (2018), Saftarina et al (2018), and Yogisutanti et al, (2020) that there was no relationship between age and work fatigue (8).…”
Section: The Effect Of Age On Work Fatiguesupporting
confidence: 70%
See 3 more Smart Citations
“…The most optimum physical capacity possessed by individual is in the age of 25-30 years old and over 30 years old, physical capacity will reduce 1% per year (Tarwaka, 2014). The result of this research supported the previous research result which revealed that age has significant effect on work fatigue (Atiqoh et al, 2014;Bongakareng, Layuk, Pesak & Danial, 2019;Rahmawati & Tualeka, 2019). This research result was not in line the research conducted by Putri (2018), Saftarina et al (2018), and Yogisutanti et al, (2020) that there was no relationship between age and work fatigue (8).…”
Section: The Effect Of Age On Work Fatiguesupporting
confidence: 70%
“…The findings obtained by Saftarina et al (2018) and Putri (2018) also supported this research results as they found that job tenure had a significant relationship with working fatigue (p = 0.041). The longer job tenure obtained a positive effect as the workers get more experiences; on the other hand, it brought a negative effect as the fatigue and boredom increased (Rahmawati & Tualeka, 2019). In line with the opinion of Atiqoh et al (2014), tenure is closely related to the adaptability of a worker to work and the work environment (Rahmawati & Tualeka, 2019).…”
Section: The Effect Of Job Tenure On the Working Fatiguementioning
confidence: 58%
See 2 more Smart Citations
“…In fact, nutrition improvement and enhancement is very important in improving health and work productivity. Research by Verawati (2017) and Rahmawati and Tualeka (2019) also conclude a weak correlation between these variables.…”
Section: The Correlation Between Nutritional Status and Work-related mentioning
confidence: 91%